Improving Cooperative Attitudes in Indonesian Language Learning Through the Cooperative Learning Model Stad Type in Class IV of SDN Kuningan Barat 01 South Jakarta - Dita Dwi Ramona Sayem; Gusti Yarmi; Herlina (PT Bukuloka Literasi Bangsa, 2026)
This study aims to improve the cooperative attitude of fourth grade students at SDN Kuningan Barat 01 through the application of the STAD cooperative learning model in Indonesian language learning. This study used the Classroom Action Research (CAR) method, which was carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. Data were obtained through observation sheets on mutual cooperation attitudes and documentation of learning activities. The results showed an increase in students' mutual cooperation attitudes, from 55% in Cycle I to 75% in Cycle II and 90% in Cycle III. These findings indicate that the STAD cooperative learning model is effective in encouraging students to work together, participate actively, and show responsibility in group activities. Thus, the application of the STAD model can be an alternative learning strategy that is relevant for strengthening character values, especially mutual cooperation attitudes in Indonesian language learning. Keywords: Mutual Cooperation Attitude, STAD, Indonesian Language Learning